2018
DOI: 10.1002/mbo3.647
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of methanogenesis by electric syntrophy with biogenic iron‐sulfide minerals

Abstract: Recent studies have shown that interspecies electron transfer between chemoheterotrophic bacteria and methanogenic archaea can be mediated by electric currents flowing through conductive iron oxides, a process termed electric syntrophy. In this study, we conducted enrichment experiments with methanogenic microbial communities from rice paddy soil in the presence of ferrihydrite and/or sulfate to determine whether electric syntrophy could be enabled by biogenic iron sulfides. Although supplementation with eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 61 publications
(95 reference statements)
0
22
0
Order By: Relevance
“…69,70 Some types of FeS compounds have been shown to enhance direct interspecies electron transfer. 59…”
Section: Resultsmentioning
confidence: 99%
“…69,70 Some types of FeS compounds have been shown to enhance direct interspecies electron transfer. 59…”
Section: Resultsmentioning
confidence: 99%
“…Nanoparticle‐assisted electron transfer is particularly important for methanogenesis that relies on close interactions between Bacteria and Archaea ; theoretical calculations indicate that interspecies electron flux via nanoparticles is about 10 6 times higher than using diffusible H 2 molecules (Cruz Viggi et al ., 2014). Consistent with this calculation, methane‐producing microbial communities enriched from paddy soils, anaerobic digesters and lake and coastal sediments display 0.3 to 4 times faster methane production rates when conductive nanoparticles are added to the cultures (Kato et al ., 2012a; Yamada et al ., 2015; Zhuang et al ., 2015, 2018; Kato and Igarashi, 2018; Rotaru et al ., 2018, 2019). In one particular case, methanogenesis was only sustainable in the presence of conductive nanoparticles (Rotaru et al ., 2019).…”
Section: Nanoparticle‐assisted Electron Transfer Among Microbial Cellsmentioning
confidence: 99%
“…Each secondary product has its own unique characteristics (such as crystal structure, particle size, redox potential, and conductivity), which determine its specific impact on the related biogeochemical processes. Recently, there are increasing studies investigating the association between biomineralization of iron (hydr)oxides and microbial methanogenesis (Jiang et al, 2013;Zhuang et al, 2015b;Zheng et al, 2017;Kato and Igarashi, 2019); biogenic magnetite and iron sulfides are demonstrated to enhance methanogenesis in soil and sediment. As the first attempt, our previous study (Tang et al, 2016) investigated the response of methanogenic activity to different transformation pathways of ferrihydrite in the artificial coculture of Geobacter and Methanosarcina.…”
Section: Introductionmentioning
confidence: 99%